2020
DOI: 10.4236/oalib.1106059
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Flour from White Bean (Phaseolus vulgaris) on Rheological, Qualitative and Nutritional Properties of the Bread

Abstract: The white bean represents the most important nutrition legume in many countries in the world, including Kosovo. It has high protein, dietary fibers and mineral content and it is mainly used in the form of cooked food. This paper has the objective to review the parameters of rheological properties, qualitative properties and nutrition values of the bread produced by adding various percentages of the flour obtained from white bean. The results from rheological analysis of the dough indicate that with the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Table 3 Shows the iron content in baby food mixes per 100 grams, where the results were 0.45 mg / 100 grams (minimum). In another study [28,29], whereas, they produced breakfast cereals using (wheat flour, mango, milk, soy flour) and the iron content in both mixtures was 7.5 mg, which is highest than of our study. When referring to Yemeni Standard Specifications no.…”
Section: Discussioncontrasting
confidence: 63%
“…Table 3 Shows the iron content in baby food mixes per 100 grams, where the results were 0.45 mg / 100 grams (minimum). In another study [28,29], whereas, they produced breakfast cereals using (wheat flour, mango, milk, soy flour) and the iron content in both mixtures was 7.5 mg, which is highest than of our study. When referring to Yemeni Standard Specifications no.…”
Section: Discussioncontrasting
confidence: 63%
“…There is not much information about the nutritional content of green beans. The authors reported ash values that ranged from 3-4.4% in white kidney beans [7,8]. Concerning MF, some of the most studied mesquite species are P. alba, P. nigra, P. pallida, P. chilensis, P. cineraria, P. tamarugo, and P. juliflora [9].…”
Section: Proximal Analysis Of Floursmentioning
confidence: 99%
“…Regarding beans in an immature form, known as a green bean, no reports of its addition in bakery products are reported. However, white kidney beans [7,8] have been successfully added to bread. Using white kidney beans, it was possible to obtain bread with a higher protein, fiber, and ash content that also had acceptable sensory (texture and flavor) characteristics and oil and water absorption changes.…”
Section: Introductionmentioning
confidence: 99%
“…Beans belong to the family of legumes which are versatile and commonly eaten food throughout the world. Even though they are economical, they are nutritious and improve diet quality and the long-term health of individuals who consume them regularly [1][2][3][4][5] . Due to the combination of nutrients found in beans, they were classified by the 2010 Dietary Guidelines for Americans as a "Unique Food," food that is a vegetable and protein, one that functions as energygiving, body-building and protective altogether 6 .…”
Section: Introductionmentioning
confidence: 99%